2008
DOI: 10.1186/1742-2094-5-42
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-Abeta28conjugate prevents Abeta-plaque deposition, but increases microhemorrhages in the brains of vaccinated Tg2576 (APPsw) mice

Abstract: Background: New pre-clinical trials in AD mouse models may help to develop novel immunogenadjuvant configurations with the potential to avoid the adverse responses that occurred during the clinical trials with AN-1792 vaccine formulation. Recently, we have pursued an alternative immunization strategy that replaces QS21 the Th1 type adjuvant used in the AN-1792 clinical trial with a molecular adjuvant, mannan that can promote a Th2-polarized immune response through interactions with mannose-binding and CD35/CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 93 publications
(121 reference statements)
2
24
0
1
Order By: Relevance
“…This is consistent with the pathological changes reported in the brain of Alzheimer's transgenic mice following A␤-based immunotherapy. 57,58 In this regard, the pathological changes in the retina of Alzheimer's mice seem to parallel those in their brain (Supplemental Figure S1, see http://ajp.amjpathol/ org). Our findings of increased microvascular deposition of A␤ support the notion that vaccination-induced antibodies solubilize A␤ plaques and promote A␤ infiltration into the perivascular space.…”
Section: Discussionmentioning
confidence: 90%
“…This is consistent with the pathological changes reported in the brain of Alzheimer's transgenic mice following A␤-based immunotherapy. 57,58 In this regard, the pathological changes in the retina of Alzheimer's mice seem to parallel those in their brain (Supplemental Figure S1, see http://ajp.amjpathol/ org). Our findings of increased microvascular deposition of A␤ support the notion that vaccination-induced antibodies solubilize A␤ plaques and promote A␤ infiltration into the perivascular space.…”
Section: Discussionmentioning
confidence: 90%
“…Given the highly variable presentation of CAA in humans, these data like the aforementioned reports are somewhat anecdotal in nature. However, this phenomena has also been seen in mice immunized with Manna-A 28 conjugates [59] or receiving passive anti-A immunotherapy [26]. Moreover, several groups report that A immunotherapy can increase microhemmorhage, though the functional significance of this "sideeffect" is unclear [26,60].…”
Section: Clearance Versus Attenuation Of Deposition?mentioning
confidence: 99%
“…Petrushina previously demonstrated that though mannan-A␤28 conjugate promotes Th2-mediated immune responses and prevents A␤-plaque deposition, it increases microhemorrhages in the brains of vaccinated Tg2576 mice (Petrushina et al, 2008). However, according to the publication by Chauhan and Siegel (2005) or Ghochikyan et al (2006), we think that the microhemorrhages in the brains reported by Petrushina may result from the mannan moiety, but not from the A␤28 moiety, of mannan-A␤28 conjugate.…”
Section: Introductionmentioning
confidence: 87%